2014
DOI: 10.1002/jmri.24751
|View full text |Cite
|
Sign up to set email alerts
|

Arterial spin labeling MRI: Clinical applications in the brain

Abstract: Visualization of cerebral blood flow (CBF) has become an important part of neuroimaging for a wide range of diseases. Arterial spin labeling (ASL) perfusion magnetic resonance imaging (MRI) sequences are increasingly being used to provide MR-based CBF quantification without the need for contrast administration, and can be obtained in conjunction with a structural MRI study. ASL MRI is useful for evaluating cerebrovascular disease including arterio-occlusive disease, vascular shunts, for assessing primary and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
133
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(136 citation statements)
references
References 65 publications
2
133
1
Order By: Relevance
“…Indeed, Jann et al showed that CBF-based FC analysis revealed greater connectivity of the DMN in the prefrontal cortex compared to BOLD, in agreement with findings by Tak et al (Tak et al, 2013). It was also found that the amplitude of low frequency fluctuation (ALFF) computed from CBF time series was significantly different across RBNs and subjects (Fig.…”
Section: Perfusion-based Functional Connectivity Mappingsupporting
confidence: 61%
See 1 more Smart Citation
“…Indeed, Jann et al showed that CBF-based FC analysis revealed greater connectivity of the DMN in the prefrontal cortex compared to BOLD, in agreement with findings by Tak et al (Tak et al, 2013). It was also found that the amplitude of low frequency fluctuation (ALFF) computed from CBF time series was significantly different across RBNs and subjects (Fig.…”
Section: Perfusion-based Functional Connectivity Mappingsupporting
confidence: 61%
“…A comprehensive overview of clinical studies using ASL can be found in a recent review Telischak et al, 2014), and will not be reiterated in this article.…”
Section: Introductionmentioning
confidence: 97%
“…44 Alternatively, arterial spin-labeling perfusion is a completely noninvasive MR imaging technique that does not require the administration of gadolinium contrast but instead uses an electromagnetic spin inversion to tag water molecules, which then serve as a freely diffusible flow tracer. 45 On the basis of our own clinical experience and a few isolated case reports, perfusion imaging in RCVS may show multifocal areas of hypoperfusion that often include cerebral watershed zones corresponding to the involved vascular territories (Fig 3). 46,47 These areas of perfusion abnormality may worsen acutely and, in some instances, progress to watershed infarction as previously discussed.…”
Section: Perfusion Imagingmentioning
confidence: 99%
“…8 pCASL MRI is a new arterial spin labelling technique that has the potential of combining advantages of continuous arterial spin labelling and pulsed arterial spin labelling. pCASL MRI is an intermediate technique between continuous arterial spin labelling and pulsed arterial spin labelling, which utilizes a series of discrete radiofrequency pulses to mimic the continuous arterial spin labelling method for spin labelling.…”
Section: Introductionmentioning
confidence: 99%